A preliminary study of low-dose angiotensin 1-7 plus the pineal hormone melatonin in the treatment of human systemic diseases other than cancer and autoimmune pathologies - Lissoni, Paolo (2021)
Fil: Lissoni, Paolo. Instituto de Medicina Biológica; Italia